Upping their number, addressing their risk. Viola singularis (Violaceae) revisited, and an evaluation of sect. Andinium, its higher taxonomic group - Watson, John Michael; Flores, Ana Rosa (Phytotaxa, 2014)
An important amendment is made to the type locality given for Viola singularis. We analyse the precarious rarity of many Viola sect Andinium taxa, including this particular species. It is only known as a solitary specimen from a single site. The combined effect of rarity and geographical remoteness on the numerical content of the section is also discussed.